Production of papaya seedlings and initial growth produced in different polyethylene recipients - Marcolin, M.; Massaroto, J. A.; Souza, R. N.; Rocha, R. R. (Scientific Electronic Archives, 2021)
The objective of this study was to evaluate the vegetative and productive performance of papaya seedlings in response to different volumes of containers. The experiment was conducted in a seedling production nursery at the State University of Mato Grosso (UNEMAT), Campus de Nova Mutum - MT, using a completely randomized design with five replications, in which four sizes of polyethylene bags were tested in the production of seedlings: 10 x 16 cm, 15 x 21 cm, 17 x 27 cm and 20 x 21 The plots were composed of 3 plants. The parameters evaluated at 70 days after sowing were: plant height, stem diameter, number of leaves, root length, green matter mass and percentage of dry weight of the stem, leaves and roots. The container 17 x 27 cm stood out from the other containers, except for the characteristics of the length of the stem, percentage of dry mass of the stem and leaves where it was equivalent to the container 20 x 21 cm and the percentage of dry mass where all containers were equivalent. The experiment showed that the 17 x 27 cm container is the most recommended for the cultivation of papaya seedlings cultivar Sunrise Solo.